Biological activity of pyrazole and imidazole-dehydroepiandrosterone derivatives on the activity of 17β-hydroxysteroid dehydrogenase. (2nd January 2016) - Cabeza, Marisa; Posada, Alejandro; Sánchez-Márquez, Araceli; Heuze, Yvonne; Moreno, Isabel; Soriano, Juan; Garrido, Mariana; Cortés, Francisco; Bratoeff, Eugene
Abstract: The enzyme type 5 17β-hydroxysteroid dehydrogenase 5 (17β-HSD5) catalyzes the transformation of androstenedione (4-dione) to testosterone (T) in the prostate. This metabolic pathway remains active in cancer patients receiving androgen deprivation therapy. Since physicians seek to develop advantageous and better new treatments to increase the average survival of these patients, we synthesized several different dehydroepiandrosterone derivatives. These compounds have a pyrazole or imidazole function at C-17 and an ester moiety at C-3 and were studied as inhibitors of 17β-HSD5. The kinetic parameters of this enzyme were determined for use in inhibition assays. Their pharmacological effect was also determined on gonadectomized hamsters treated with Δ 4 -androstenedione (4-dione) or testosterone (T) and/or the novel compounds. The results indicated that the incorporation of a heterocycle at C-17 induced strong 17β-HSD5 inhibition. These derivatives decreased flank organ diameter and prostate weight in castrated hamsters treated with T or 4-dione. Inhibition of 17β-HSD5 by these compounds could have therapeutic potential for the treatment of prostate cancer and benign prostatic hyperplasia.